Toward a Global Sharia-Compliant Regulatory Architecture: A Critical Reassessment of Islamic Economic Law in the Digital Age - Fuad Fazil Osmanov; Zohr Isa Babazade; Asma Elmar Mansurzada (Mabadi Iqtishad Al Islami, 2025)
This study critically reassesses Islamic economic law in response to the accelerating digital transformation reshaping global financial ecosystems. Drawing on classical jurisprudential sources, international Sharia standards, and contemporary literature on Islamic fintech, the research employs a qualitative library-based methodology to evaluate how digital innovations—particularly AI, blockchain, digital assets, and Islamic fintech platforms—challenge existing regulatory structures across Muslim jurisdictions. The findings reveal substantial fragmentation in Sharia governance, inconsistencies in regulatory interpretation, and limited technical capacity, which collectively hinder the development of a cohesive global framework. The study argues that the integration of Maqasid al-Shariah offers a robust ethical and legal foundation for constructing a global Sharia-compliant regulatory architecture capable of addressing cybersecurity risks, algorithmic bias, consumer protection gaps, cross-border inconsistencies, and the complexities of emerging technologies. The analysis highlights the need for harmonized standards, AI ethics protocols, enhanced RegTech adoption, and dynamic regulatory sandboxes to balance innovation with Sharia compliance. Ultimately, the research proposes a forward-looking model that embeds Islamic ethical principles within contemporary digital governance, ensuring that Islamic finance remains resilient, transparent, and socially responsible in the digital age.